KARAKTERISTIK BATAKO DARI CAMPURAN SEMEN DAN SERBUK GERGAJIAN KAYU PALAPI (Hertiera sp) - Wahyudi, Nuryanto Hafid; Erniwati, Erniwati; Hapid, Abdul (Universitas Tadulako, 2017)
This research was conducted on February up to the month ofÂ May 2015 in Machine Laboratory of Technique Faculty and Forestry Laboratory of Forestry Faculty of Tadulako University. The research steps were preparing material, making sample and testing sample. This research applied Complete Random Design with 5 repetitions and treatments, they were comparison of cement and sawdust composition that consisted of 4;1:1, 1:3, 1:5 and 1:7.The result of the research showed that the comparison rate of adobe water absorptionÂ was on 1:1 (17%), 1:3 (54%), 1:5 (61%), 1:7 (71%). Fault strength was on 1:1 (2,907 kg/cm2), 1:3 (0,956 kg/cm2), 1:5 (0,822 kg/cm2), 1:7 (0,975 kg/cm2) comparison. Bending Strength was on 1:1 (10,914 kg/cm2), 1:3 (3,911 kg/cm2), 1:5 (3,197 kg/cm2), 1:7 (3,135 kg/cm2). Pressing Strength was on 1:1 (25,4 kg/cm2), 1:3 (5,88 kg/cm2), 1:5 (2,9 kg/cm2), 1:7 (3,13 kg/cm2).Kata kunci : Palapi wood, Sawdust, Adobe